Ben ve Biz Arasında: Anadolu Türk-İslam Kültüründe Bir Arada Yaşama Tecrübesi - Çapcıoğlu, İhsan (Fırat University, 2012)
Throughout history Turks have coexisted with members of different race and faiths. After this experience of living together merged with Islamic practices and customs following Islamization of Turks, a unique experience, form and conscience of ‘living together’ emerged. In this paper, the coexisting experience in Anatolian Turkish-Islamic Culture, in particular in the context of its examples during Ottoman period with their sociological background and outcomes, has been explored.
BETWEEN I AND WE: COEXISTENCE EXPERIENCE IN ANATOLIAN TURKISH-ISLAMIC CULTURE
Keywords: Religious Studies; Din Araştırmaları